2013
DOI: 10.1002/cssc.201300457
|View full text |Cite
|
Sign up to set email alerts
|

Wide Electrochemical Window of Supercapacitors from Coffee Bean‐Derived Phosphorus‐Rich Carbons

Abstract: Phosphorus-rich carbons (PCs) were prepared by phosphoric acid activation of waste coffee grounds in different impregnation ratios. PCs were characterized by nitrogen and carbon dioxide adsorption and X-ray photoelectron spectroscopy. The results indicate that the activation step not only creates a porous structure, but also introduces various phosphorus and oxygen functional groups to the surface of carbons. As evidenced by cyclic voltammetry, galvanostatic charge/discharge, and wide potential window tests, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(76 citation statements)
references
References 49 publications
3
73
0
Order By: Relevance
“…Moreover, they assigned the enhanced oxidation resistance to the physical blockage of active sites by phosphate groups [33], thus, using arguments employed in the thermal-oxidative gasification of carbons [35][36][37][38][39][40]. On the other hand, instead of an effect on the oxidation resistance, Huang et al have recently objected that the P-groups, especially polyphosphates, play a critical role in stabilizing the surface of carbons during the reversible electrochemical hydrogen storage at low potentials [34].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they assigned the enhanced oxidation resistance to the physical blockage of active sites by phosphate groups [33], thus, using arguments employed in the thermal-oxidative gasification of carbons [35][36][37][38][39][40]. On the other hand, instead of an effect on the oxidation resistance, Huang et al have recently objected that the P-groups, especially polyphosphates, play a critical role in stabilizing the surface of carbons during the reversible electrochemical hydrogen storage at low potentials [34].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Thus, whereas the presence of oxygen groups has been commonly found to be detrimental to the electrochemical stability [30], a beneficial influence of certain surface functionalities of nitrogen [31,32] or phosphorus [33,34] has been claimed. In spite of the promising perspectives for various applications, to the knowledge of the authors, there are few works proposing an enhanced electrochemical stability induced by Pfunctionalities and, in all cases, applied for widening the stability potential window of carbon-based supercapacitors [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that P-doped biomass-derived carbon can also widen the electrochemical window of supercapacitors [132,180]. For example, Huang et al [180] prepared phosphorus-rich carbons (PCs) through phosphoric acid activation of waste coffee grounds.…”
Section: Biomass-derived Carbon Materials For Energy Storage Applicatmentioning
confidence: 99%
“…All the characteristics strongly suggest that biomass-derived carbon could be qualified for the electrode of supercapacitors. To date, various biomass-derived carbon materials with high SSA, abundant pore structure and modified functional groups have been prepared, such as the stems [87,102,157,[177][178][179], leaves [34,90,101,103,126], seeds [48,77,79,154], fructus [180][181][182], pericarp [88,89] of plants, nut shells [94,143,[183][184][185], fungi [53,109,[186][187][188], abandoned food [96,131,189], shellfish [49,72,133], animal tissue [112,115,124], polysaccharide [44,85,147,155,190], protein [137].…”
Section: Biomass-derived Carbon Materials For Energy Storage Applicatmentioning
confidence: 99%